BUSINESS’S CORPORATE SOCIAL RESPONSIBILITY AT THE POST-SOVIET AREA: FEATURES OF ASSESSING THE EFFECTIVENESS OF AN INDUSTRY ORGANIZATION’S SOCIAL SPHERE - Malei, Alena; Afanasyeva, Katsiaryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The global trend of developing the institute of social responsibility of businesses leads to the need to train specialists with new professional competences in the practical application of the concept of corporate social responsibility, taking into account the peculiarities of the social sphere of industrial organizations in the post-Soviet countries.   The purpose of this study is to develop a methodical toolkit to assess the effectiveness of the management of the social sphere of industrial enterprises within the framework of the concept of corporate social responsibility. Methods of theoretical and empirical research, methodological techniques and approaches used in the analysis of the activities of enterprises by Western experts, as well as their modifications, allowing to take into account the specifics of the economic situation of the post-Soviet countries, were used as methodological tools. The article discusses the methodological features of assessing the effectiveness of an industrial organizations' social sphere within the framework of applying the CSR concept at the post-Soviet space. The authors propose a system for evaluating the effectiveness and forecasting the activity of the social sphere of industrial organizations in four key areas: social, economic, organizational, and technological efficiency, which meet the main targets of the activities of such entities. The authors have developed a new system of balanced indicators that allows to assess the efficiency of the functioning of cultural and recreational facilities that are on the balance sheet of industrial organizations, focusing on the interests of various parties: both external and internal stakeholders, based on the optimal ratio of economic benefit and social result. The new CSR procedure related to the integration of social reporting with the system of key performance indicators will allow monitoring the effectiveness of the industrial organizations' social sphere by aggregated indicators within the framework of management by goals and is a powerful tool for strategic planning of their activities.